Projection of the Flipped Learning Methodology in the Teaching Staff of Cross-Border Contexts - Jesús López Belmonte; Santiago Pozo Sánchez; María José del Pino Espejo (Springer, 2019)
Technological impact and immigration have resulted in ICT playing a significant role in educational adaptation to multicultural environments. This study focuses on flipped learning as an innovative teaching method. The overall objectives of this research are, on the one hand, to carry out a review of the scientific literature about flipped learning, and, on the other hand, to know the extent of its scope amongst teaching staff in cross-border regions. To achieve these objectives, a quantitative method has been developed through a descriptive model. 316 teachers from different educational centres of the Spanish Autonomous City of Ceuta (Spain) were selected as a sample, and an ad hoc questionnaire was used as an instrument for collecting personal data. Statistical procedures were performed through SPSS software, using location and scattering parameters (median and standard deviation), measurements (Pearson's asymmetry coefficient and Fisher's pointing coefficient) and association tasks between variables. The results show that teachers claim to have the necessary knowledge to implement flipped learning in their programmes, but they still have certain deficiencies in their specific training. A significant number of these teachers do not use it because they lack training and digital assets, and also because of a certain apprehension towards innovative practices. The main benefits include the improvement in the student's autonomy, their participation, interaction and motivation, as well as the teachers' satisfaction. Regarding the teachers' perception, it therefore follows that flipped learning contributes to the attention towards diversity created by the multicultural environments, which in this case is a result of the migration phenomenon.